A Method to Compare ICF and SNOMED CT for Coverage of U.S. Social Security Administration’s Disability Listing Criteria - Tu, Samson W. (AMIA Annu Symp Proc, 2015)
We developed a method to evaluate the extent to which the International Classification of Function, Disability, and Health (ICF) and SNOMED CT cover concepts used in the disability listing criteria of the U.S. Social Security Administration’s “Blue Book.” First we decomposed the criteria into their constituent concepts and relationships. We defined different types of mappings and manually mapped the recognized concepts and relationships to either ICF or SNOMED CT. We defined various metrics for measuring the coverage of each terminology, taking into account the effects of inexact matches and frequency of occurrence. We validated our method by mapping the terms in the disability criteria of Adult Listings, Chapter 12 (Mental Disorders). SNOMED CT dominates ICF in almost all the metrics that we have computed. The method is applicable for determining any terminology’s coverage of eligibility criteria.